2009
DOI: 10.1002/mnfr.200800571
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and DNA interactions are not involved in Enniatin‐ and Beauvericin‐mediated apoptosis induction

Abstract: The fusariotoxins beauvericin (BEA) and the structurally related enniatins (ENN) are frequent contaminants of grain-based food and feed. They exert potent cytotoxic activities based on apoptosis induction. Since it is known, that reactive oxygen species (ROS) and DNA damage lead to apoptotic cell death, this study aimed to clarify whether oxidative stress and DNA interactions are involved in ENN- and BEA-induced cytotoxicity. Diverse cellular and molecular assays indicated that oxidative stress does not contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 53 publications
2
50
0
1
Order By: Relevance
“…This conclusion is supported by a previous study predicting that ROS were not directly involved in enniatin-induced cytotoxic effects. 8 Taking in to account the new knowledge on lysosomal cell death, it is tempting to favor the lysosomal−mitochondrial death pathway. 12,21 Thus, released lysosomal materials could have affected the mitochondria leading to MOMP and the production of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is supported by a previous study predicting that ROS were not directly involved in enniatin-induced cytotoxic effects. 8 Taking in to account the new knowledge on lysosomal cell death, it is tempting to favor the lysosomal−mitochondrial death pathway. 12,21 Thus, released lysosomal materials could have affected the mitochondria leading to MOMP and the production of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…These report that enniatin- and beauvericin-induced cell death is primarily based on apoptosis induction via the mitochondrial pathway [22,27,28] or necrosis-induction via lysosomal damage [29,30,31]. Contrasting reports have been made regarding enniatin- and beauvericin-induced oxidative stress [32,33,34]. Furthermore, both compounds inhibit the activity of acyl-CoA:cholesterol acyltransferase (ACAT), a protein of the endoplasmic reticulum, which produces cholesteryl esters from cholesterol.…”
Section: Introductionmentioning
confidence: 99%
“…Dornetschuber et al, demonstrated that Enn cytotoxicity did not involve oxidative stress in HL-60 leukemia cells or cervix carcinoma KB-3-1 cells, or cause DNA damage in the form of DNA intercalation (Dornetshuber et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%